2022
DOI: 10.1167/iovs.63.11.16
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Loss of Contrast Decrement Responses in Human Glaucoma

Abstract: Purpose The purpose of this study was to determine whether glaucoma in human patients produces preferential damage to OFF visual pathways, as suggested by animal experimental models, patient electroretinogram (ERG), and retinal imaging data. Methods Steady-state visual evoked potentials (SSVEPs) were recorded monocularly from 50 patients with glaucoma and 28 age-similar controls in response to equal Weber contrast increments and decrements presented using 2.73 hertz (Hz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Their results confirmed that cortical responses to decrements are normally larger and faster than responses to increments in healthy persons, but in the subgroup of eyes with moderate-to-advanced glaucoma (worse than −6 dB visual field mean deviation), decrement responses were statistically significantly reduced and delayed and the normally strong ON–OFF asymmetry was diminished. 28 Although these results were interpreted as representing preferential damage of the OFF pathway in glaucoma, there was a trend evident in the subgroup of eyes with mild glaucoma for greater loss of increment (ON pathway) responses than OFF responses. Thus, again, it may be that relative functional loss of ON and OFF pathways depends on the stage of glaucoma severity with relatively worse OFF pathway function occurring only at later stages.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Their results confirmed that cortical responses to decrements are normally larger and faster than responses to increments in healthy persons, but in the subgroup of eyes with moderate-to-advanced glaucoma (worse than −6 dB visual field mean deviation), decrement responses were statistically significantly reduced and delayed and the normally strong ON–OFF asymmetry was diminished. 28 Although these results were interpreted as representing preferential damage of the OFF pathway in glaucoma, there was a trend evident in the subgroup of eyes with mild glaucoma for greater loss of increment (ON pathway) responses than OFF responses. Thus, again, it may be that relative functional loss of ON and OFF pathways depends on the stage of glaucoma severity with relatively worse OFF pathway function occurring only at later stages.…”
Section: Discussionmentioning
confidence: 89%
“…Another recent study, by Norcia et al, 28 used an elegant approach for analysis of steady-state visual evoked cortical responses to sawtooth increment and decrement stimuli favoring ON and OFF visual pathways, respectively. Their results confirmed that cortical responses to decrements are normally larger and faster than responses to increments in healthy persons, but in the subgroup of eyes with moderate-to-advanced glaucoma (worse than −6 dB visual field mean deviation), decrement responses were statistically significantly reduced and delayed and the normally strong ON–OFF asymmetry was diminished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means we have a near absent quantitative understanding of the supra-threshold visual experience across the visual field of patients with ocular pathology. We have previously used the SSVEP to demonstrate an OFF-pathway vulnerability in Glaucoma (Norcia et al, 2022), but at a single contrast. Recently, Bham et al (2020) measured behavioural contrast matching thresholds in patients with partial Glaucomatous field loss.…”
Section: Implications For the Assessment Of Ocular Pathologymentioning
confidence: 99%
“…Describing the degree of ON-and OFFpathway VF asymmetry may then allow us to better simulate human behavior. Additionally, it would provide a more detailed understanding of the perceptual experiences of individuals with pathology that affects one pathway more than the other, like amblyopia (Pons et al, 2019) and glaucoma (Norcia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%